1988
DOI: 10.1063/1.455720
|View full text |Cite
|
Sign up to set email alerts
|

Unoccupied molecular orbitals of aromatic hydrocarbons adsorbed on Ag(111)

Abstract: The unoccupied π* bands of epitaxial overlayers of benzene, naphthalene, anthracene, tetracene, perylene, and coronene on a Ag(111) surface have been studied by angle resolved inverse photoemission spectroscopy. A comparison with HAM/3 MO calculations and electron transmission gas phase measurements enables the assignment of the π* affinity levels of these organic systems. In conjunction with previous angle resolved photoemission, optical absorption, and near edge x-ray absorption studies a complete picture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
73
5

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 35 publications
13
73
5
Order By: Relevance
“…Experimental studies have reported that both anthracene and pentacene monolayers weakly adsorb on Ag(111), as characteristic of physisorption or weak chemisorption [5][6][7][8][9][10] , which suggests that van der Waals interactions (vdW) play an important role in the binding of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have reported that both anthracene and pentacene monolayers weakly adsorb on Ag(111), as characteristic of physisorption or weak chemisorption [5][6][7][8][9][10] , which suggests that van der Waals interactions (vdW) play an important role in the binding of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…1 Yet the available experimental data on this interface is limited. 1,10,[33][34][35] The emphasis in the present study is placed on structural data collected with scanning tunneling microscopy (STM) and low energy electron diffraction (LEED); in particular we present a refined phase diagram of the Tc/Ag(111) interface in the coverage range 0 to 2.4 MLs. Based on the structural data presented here, electronic structure studies, 35 kinetic growth studies, etc., may be performed in the future.…”
mentioning
confidence: 99%
“…130,131 On the basis of these data, the E LUMO value was estimated to be À0:86 eV for Nph single crystal. In addition, in the experimental results of IPES for highly ordered Nph thin film on Ag(111) reported by Frank et al, 123 the energy of the LUMO from the vacuum level has been reported to be À1:1 AE 0:15 eV. Because of image charges on the metal substrate, this energy may be a little larger than the intrinsic energy of the bulk.…”
Section: Insight Into Isomers: Comparison To the Bulkmentioning
confidence: 94%
“…122 In strong contrast, there are rather few reliable experimental data for P À , while it is currently under investigation by means of inverse photoemission spectroscopy (IPES). [123][124][125][126] Finite-size cluster anions of -conjugated molecules are viewed as an embryo of a negative polaron in organic molecular solids, because the single excess electron doped in the cluster is stabilized by the finite number of polarized molecules, i.e., a finite-size polarization cloud. As shown in Fig.…”
Section: Research Backgroundmentioning
confidence: 99%